Crohn's Disease Initially Accompanied by Deep Vein Thrombosis and Ulnar Neuropathy without Metronidazole Exposure (Gut and Liver, 2013)
Extraintestinal manifestations are not uncommon in Crohn's disease, and a thromboembolic event is a disastrous potential complication. Deep vein thrombosis is the most common manifestation of a thromboembolic event and typically occurs in association with active inflammatory disease. Peripheral neuropathy in Crohn's disease has rarely been reported and is considered an adverse effect of metronidazole therapy. Here, we describe a patient who was initially diagnosed with Crohn's disease complicated with deep vein thrombosis and ulnar neuropathy without metronidazole exposure. The simultaneous occurrence of these complications in the early stage of Crohn's disease has never been reported in the English literature.